Diagnostic findings and successful management of central diabetes insipidus following a self-inflicted penetrating brain injury in a dog - Lacqua, Andrew J.; Rozanski, Elizabeth A.; Dry, Dylan A.; Gregorich, Scott L.; Sato, Amy F. (Brazilian Journal of Veterinary Medicine, 2021)
A 6-year-old 12 kg male neutered mixed breed dog presented in lateral recumbency with dysphoria and vocalization following a self-inflicted fork impalement injury. Computed tomography (CT) was performed which showed a penetrating wound through the right orbit, into the calvarium, and through the brain parenchyma. The dog was hospitalized with supportive care, sedatives, analgesia, antiepileptics, anti-inflammatories, antibiotics, and desmopressin acetate (DDAVP) to control post-traumatic central diabetes insipidus (PTCDI) which developed during recovery. Magnetic resonance imaging (MRI) findings 16 days later revealed resolving ventricular hemorrhage and mild perilesional edema and inflammation. Normal mentation and ambulation slowly returned and 3 months later the dog was clinically normal. To the author’s knowledge, this is the first report of a self-inflicted penetrating brain injury in a dog. This case demonstrates successful medical management of a dog with a traumatic brain injury (TBI) and PTCDI which is an uncommon occurrence in veterinary medicine.